2002
DOI: 10.1007/s00705-002-0895-2
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable morphological diversity of viruses and virus-like particles in hot terrestrial environments

Abstract: Electron microscopic studies of the viruses in two hot springs (85 degrees C, pH 1.5-2.0, and 75-93 degrees C, pH 6.5) in Yellowstone National Park revealed particles with twelve different morphotypes. This diversity encompassed known viruses of hyperthermophilic archaea, filamentous Lipothrixviridae, rod-shaped Rudiviridae, and spindle-shaped Fuselloviridae, and novel morphotypes previously not observed in nature. Two virus types resembled head-and-tail bacteriophages from the families Siphoviridae and Podovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 45 publications
1
69
0
1
Order By: Relevance
“…Viruses have been identified in all known extreme environments: hypersaline (Oren et al, 1997;Dyall-Smith et al, 2003;Pagaling et al, 2007;Sime-Ngando et al, 2010), alkaline lakes (Jiang et al, 2004), deserts (Prigent et al, 2005), polar regions (Maranger et al, 1994;Kepner et al, 1998;Borriss et al, 2003;Gowing, 2003), acid mine drainages (Kyle et al, 2008a), deep subsurface rocks (Bird et al, 2001;Kyle et al, 2008b), and in hydrothermal environments. The search for new viruses in the latter environment has been especially fruitful, following the pioneering work of Wolfram Zillig on the viruses of hyperthermophilic Archaea (Martin et al, 1984;Rice et al, 2001;Rachel et al, 2002). Many new viral families that infect hyperthermophilic Archaea in terrestrial and marine hot springs have been identified (Geslin et al, 2003b;Ortmann and Suttle, 2005;Geslin et al, 2005;Prangishvili et al, 2006a;Ortmann et al, 2006;Le Romancer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses have been identified in all known extreme environments: hypersaline (Oren et al, 1997;Dyall-Smith et al, 2003;Pagaling et al, 2007;Sime-Ngando et al, 2010), alkaline lakes (Jiang et al, 2004), deserts (Prigent et al, 2005), polar regions (Maranger et al, 1994;Kepner et al, 1998;Borriss et al, 2003;Gowing, 2003), acid mine drainages (Kyle et al, 2008a), deep subsurface rocks (Bird et al, 2001;Kyle et al, 2008b), and in hydrothermal environments. The search for new viruses in the latter environment has been especially fruitful, following the pioneering work of Wolfram Zillig on the viruses of hyperthermophilic Archaea (Martin et al, 1984;Rice et al, 2001;Rachel et al, 2002). Many new viral families that infect hyperthermophilic Archaea in terrestrial and marine hot springs have been identified (Geslin et al, 2003b;Ortmann and Suttle, 2005;Geslin et al, 2005;Prangishvili et al, 2006a;Ortmann et al, 2006;Le Romancer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One group of ecosystems which has yielded exciting new results is geothermally heated hot aquatic environments. Screening for viruses in terrestrial hot springs with temperatures above 80°C in Iceland (20) and in Yellowstone National Park (13,15) has revealed numerous, different virus morphotypes, many of which have not been previously observed in nature. Several of the isolated viruses infect hyperthermophilic archaea from the Crenarchaeota kingdom, and they all have double-stranded DNA (dsDNA) genomes.…”
mentioning
confidence: 97%
“…To date, of the Ϸ5,100 known viruses, only 36 have been isolated from Archaea [International Committee on Taxonomy of Viruses, www.ncbi.nlm.nih.gov͞ICTV (1)]. Viruses and viruslike particles have been isolated from high-temperature (Ն80°C) acidic pH (Ͻ3.0) terrestrial environments throughout the world (2)(3)(4). Typically, these environments are found in thermal features such as boiling hot springs, mud pots, fumaroles, and geysers, with a wide range of geochemical compositions (5,6).…”
mentioning
confidence: 99%